Plasma Transferred Arc Welding of Stellite 6 Alloy on Stainless Steel for Wear Resistance. (2016) - Ferozhkhan, Mohammed Mohaideen; Duraiselvam, Muthukannan; kumar, Kottaimathan Ganesh; Ravibharath, Rajanbabu
Abstract: Austenitic stainless steel was deposited on 9Cr-1Mo steel (ASME Grade 91) by flux cored arc welding process and above that Stellite 6 (Co-Cr alloy) was coated by plasma transferred arc welding process to improve wear resistance for high temperature valves applications. Microstructural characterization was carried out on Stellite 6 coatings and hardness and chemical composition were measured by vicker's hardness tester and optical emission spectrometer respectively. The impact of alloying elements in Stellite 6 deposits and fusion line of Stellite 6 and stainless steel were analyzed by electron dispersive spectroscopy line scan. It was observed that dilution of Iron in PTA welding deposit in Stellite 6 is below 2% and hardness of more than 600 HV0.3 was obtained. Microstructure of Stellite 6 consisted of Co - solid solution matrix with dendritic structure and interdendritic eutectic carbides which provides the hardness. Pin-on-disc tests were carried out at 400 °C and characterized using scanning electron microscope of worn out surfaces. The wear mechanism was identified as delamination and abrasive wear in the worn-out surfaces as observed. Abrasive form of wear was reported due to the presence of alloying elements such as Co, Cr & W.